2019
DOI: 10.1002/ajmg.a.61201
|View full text |Cite
|
Sign up to set email alerts
|

Loss of function BMP4 mutation supports the implication of the BMP/TGF‐β pathway in the etiology of combined pituitary hormone deficiency

Abstract: Despite BMP4 signaling being critical to Rathke's pouch induction and maintenance during early stages of pituitary development, its implication in the etiology of combined pituitary hormone deficiency (CPHD) and other clinical presentations of congenital hypopituitarism has not yet been definitely demonstrated. We report here the first CPHD patient with a de novo pathogenic loss-of-function variant in BMP4. A 6-year-old boy, with macrocephaly, myopia/astigmatism, mild psychomotor retardation, anterior pituitar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…In another study Simm et al (45) reported two new genes contributing to CPHD, SLC20A1, and SLC15A4 and evidenced that a significant portion of cases arise as a de novo event. Another study utilizing NGS sequencing also shed a new light on the combination of rare variants in different genes that might explain the incomplete penetrance in CPHD and the complexity of the disorder (46,47). In conclusion, we confirmed the major contribution of PROP1 gene mutations in CPHD.…”
Section: Discussionsupporting
confidence: 73%
“…In another study Simm et al (45) reported two new genes contributing to CPHD, SLC20A1, and SLC15A4 and evidenced that a significant portion of cases arise as a de novo event. Another study utilizing NGS sequencing also shed a new light on the combination of rare variants in different genes that might explain the incomplete penetrance in CPHD and the complexity of the disorder (46,47). In conclusion, we confirmed the major contribution of PROP1 gene mutations in CPHD.…”
Section: Discussionsupporting
confidence: 73%
“…Genetic investigations embrace both pragmatic and research-based activities and new genetic associations are being identified as new technologies become more sensitive, cheaper, and widely applied. Novel genes and genetic pathways are being identified that affect pituitary function and are associated with post-natal growth failure, such as bone morphogenic protein ( BMP ) gene mutations ( 64 ), and the multiple genes involved in RASopathies, including some, such as LZTR1 mutations, that correlate with the Noonan syndrome phenotype ( 65 , 66 ). Many of these short stature genetic variants respond to GH therapy, although not all ( 17 , 64 , 67 ).…”
Section: Genomics In Precision Medicinementioning
confidence: 99%
“…Novel genes and genetic pathways are being identified that affect pituitary function and are associated with post-natal growth failure, such as bone morphogenic protein ( BMP ) gene mutations ( 64 ), and the multiple genes involved in RASopathies, including some, such as LZTR1 mutations, that correlate with the Noonan syndrome phenotype ( 65 , 66 ). Many of these short stature genetic variants respond to GH therapy, although not all ( 17 , 64 , 67 ). Hence, clinicians should be continuously up-dated of new developments and actively encouraged to build working relationships with genetic laboratories to discuss the indications and potential treatment options ( 17 ).…”
Section: Genomics In Precision Medicinementioning
confidence: 99%
“…Genetic heterogeneity and variable penetrance of this mutation makes genetic diagnosis difficult considering that posterior pituitary ectopia may not present hormonal disturbance [ 25 ]. Additionally, as proposed by Rodriguez-Contreras [ 26 ], an oligogenic inheritance may contribute to modify phenotypic expressivity of BMP4 pathogenic variants.…”
Section: Discussionmentioning
confidence: 99%